In vitro and in vivo effect of HPMA copolymer-bound doxorubicin targeted to transferrin receptor of B-cell lymphoma 38C13 - Kovár, M; Strohalm, J; Ulbrich, K; Ríhová, B (Journal of drug targeting, 2002)
N-(2-Hydroxypropyl)methacrylamide (HPMA) copolymers containing the anticancer agent doxorubicin and targeted to the transferrin receptor either with anti-mouse CD71 monoclonal antibody (mAb) or with transferrin were synthesized to evaluate their binding and anti-proliferative activity in vitro and anti-tumor potential against 38C13 B-cell lymphoma in vivo. Both the doxorubicin and the targeting moieties were bound to HPMA copolymer chain by aminolysis via a Gly-Phe(D,L)-Leu-Gly spacer to ensure controlled intracellular release of the conjugated drug. We demonstrated that HPMA copolymer-bound doxorubicin targeted to the transferrin receptor with anti-mouse CD71 mAb strongly retards tumor growth, prolongs the survival and completely cures three out of nine experimental mice with established 38C13 tumors. The conjugate targeted with transferrin was less effective in vitro as well as in vivo. It completely cured only one out of seven experimental mice. Free or non-targeted HPMA copolymer-bound doxorubicin showed only a mild anti-tumor effect within the therapeutic schedule used. In vitro, HPMA copolymer-bound doxorubicin targeted with anti-mouse CD71 mAb shows approximately 4-fold higher cytotoxic effect than HPMA copolymer-bound doxorubicin targeted with transferin and 9-fold higher cytotoxic effect than non-targeted HPMA copolymer-bound doxorubicin.
Keywords: doxorubicin; monoklonální protilátky; Transferrin; protinádorová antibiotika; ligandy; Mice, Inbred C3H; indikátory a reagencie; Lymphoma, B-Cell; Ligands; B-buněčný lymfom; methakryláty; Receptors, Transferrin; buněčné dělení; myši inbrední C3H; Flow Cytometry; transferin; průtoková cytometrie; Animals; Cell Division; zvířata; Antibiotics, Antineoplastic; Indicators and Reagents; Biotin; myši; Antibodies, Monoclonal; Mice; Methacrylates; Doxorubicin; receptory transferinu; biotin